SAFETY AS AN ELEMENT OF CREATING COMPETITIVE ADVANTAGE AMONG AIRLINES GIVEN THE EXAMPLE OF THE AIRBUS A350 XWB AND THE BOEING 787 DREAMLINER AIRCRAFT - Marcin RUTKOWSKI (Scientific Journal of Silesian University of Technology. Series Transport)
The competitive advantage of the passenger air transport market is a significant part of airline operations. An important element, a condition that may determine the achievement of competitive advantage, is the issue of safety, which also applies to the operation of aircraft. An example of creating an effective competitive advantage may be the operation of a new aircraft by air carriers. This article presents the process of creating a competitive advantage on the example of the Airbus A350 XWB and the Boeing 787 Dreamliner aircraft considering the safety aspect, which in the case of new means of transport in civil aviation may primarily concern the seeming childhood diseases occurring in the initial use of new aircraft. This article, in the form of comparative analysis, indicates the key features that determine the attractiveness of the new aircraft as a product on the passenger air transport market. Secondary data on the characteristics of the Airbus A350 XWB aircraft were used and compared with the data of the Boeing 787 Dreamliner to illustrate the properties that may indicate the manufacturer's superiority. Furthermore, this article proposes a scheme of creating competitive advantage in passenger air transport, which can be a model for creating a competitive advantage in civil aviation. The close relationship between the economic and technological aspects in creating competitive advantage was buttressed as well. This article also analysed secondary data related to the number of ordered and used aircraft and aviation events registered on the website: https://aviation-safety.net [8], which could have an impact on the level of safety of flight operations. Brought to the fore were situations in which the seeming childhood diseases in aircraft operated by the American manufacturer, Boeing 787 Dreamliner, such as defects in engines, power elements and risks associated with the use of composite materials, which were first used on such a large scale in the construction of wide-body aircraft.